"I felt that it was not for me": Symbolic violence and exclusion in the selection tests for entry into school bands (Research, Society and Development, 2025)
The objective of this study is to discuss the selection tests based on previous musical skills as an entry procedure in school marching bands. The qualitative methodology was based on the use of narrative interviews as data collection instruments. In this perspective, we interviewed ten former members of different school marching bands from João Pessoa (Brazil), who did not follow music as a profession, higher or professional studies in the area. The data indicates that seven of the ten research collaborators revealed that they were submitted to musical selection tests as a requirement to participate in school bands. It is discussed, therefore, the misconceptions, exclusions and violence produced and reinforced by selection based on previous musical skills. It is found that these tests are applied as procedures for entry into bands, disregarding the life trajectories and different musical experiences of students. The tests can serve as a "court" that labels as "not talented" students who have not had a previous musical experience. It is concluded that the selection tests based on previous musical skills can serve as instruments of exclusion and symbolic violence.